2020
DOI: 10.3390/ijms21207723
|View full text |Cite
|
Sign up to set email alerts
|

RAGE Up-Regulation Differently Affects Cell Proliferation and Migration in Pancreatic Cancer Cells

Abstract: The receptor for advanced glycation end products (RAGE) contributes to many cellular aspects of pancreatic cancer including cell proliferation, migration, and survival. Studies have shown that RAGE activation by its ligands promotes pancreatic tumor growth by stimulating both cell proliferation and migration. In this study, we investigated the effect of RAGE up-regulation on the proliferation and migration of the human pancreatic cancer Panc-1 cell-line. We show that moderate overexpression of RAGE in Panc-1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Besides AGEs itself, stimulated RAGE expression also contributes to cell proliferation. Overexpression of RAGE in pancreatic cells showed increased cell proliferation, and silencing reduced the RAGE-induced proliferation [ 51 ]. In addition, other cells also showed cell proliferation, corresponding with RAGE expression [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides AGEs itself, stimulated RAGE expression also contributes to cell proliferation. Overexpression of RAGE in pancreatic cells showed increased cell proliferation, and silencing reduced the RAGE-induced proliferation [ 51 ]. In addition, other cells also showed cell proliferation, corresponding with RAGE expression [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…RAGE expression is upregulated in a vast majority of cancers, but its expression is very low under physiological conditions. Specific examples of types of cancer in which RAGE expression is upregulated include colorectal cancer ( 32 ), pancreatic cancer ( 33 ), prostate cancer ( 34 ), lung cancer ( 35 ) and breast cancer, and in breast cancer, it has been reported that the RAGE rs1800624 polymorphism may increase the risk of breast cancer ( 36 ).…”
Section: Tages In Cancermentioning
confidence: 99%
“…On the other hand, tumor-suppressor factors such as miRNA-573 suppress PC growth via TSPAN1 down-regulation [ 89 ]. Hence, the process of PC growth seems to be complicated and each gene can target various downstream targets to modulate PC progression [ 90 ]. The aim of current section is to show that how siRNAs can be applied in targeting pathways related to the aberrant growth of PC cells.…”
Section: Sirna and Pancreatic Cancer Therapymentioning
confidence: 99%